2014
DOI: 10.1186/1471-2393-14-91
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with severe maternal morbidity and near miss in the São FranciscoValley, Brazil: a retrospective, cohort study

Abstract: BackgroundMaternal mortality remains a major public health issue worldwide, with persistent high rates prevailing principally in underdeveloped countries. The objective of this study was to determine the risk factors for severe maternal morbidity and near miss (SMM/NM) in pregnant and postpartum women at the maternity ward of the Dom Malan Hospital, Petrolina, in northeastern Brazil.MethodsA retrospective, cohort study was conducted to evaluate the sociodemographic and obstetric characteristics of the women. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
36
0
32

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 37 publications
(57 reference statements)
10
36
0
32
Order By: Relevance
“…61 In several studies, previous or current cesarean section was associated to MNM/ESMM/SMM. 21,22,24,25,27,29,34,52 Only one study showed cesarean section as a protective factor. 17 The maternal near miss rate for cesarean section was 91 cases/1,000 deliveries whereas the incidence rate on vaginal delivery was 16 /1,000 deliveries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 In several studies, previous or current cesarean section was associated to MNM/ESMM/SMM. 21,22,24,25,27,29,34,52 Only one study showed cesarean section as a protective factor. 17 The maternal near miss rate for cesarean section was 91 cases/1,000 deliveries whereas the incidence rate on vaginal delivery was 16 /1,000 deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…60 On the other hand, a protective effect was observed in relation to MNM for the beneficiary families of Bolsa Família Program 55 (a Government program for extreme low income family to receive like an allowance) and the protective association of prenatal care regarding MNM was well evidenced. 18,24,28,46 It ratifies that complementing both politics and income as a basic care can reverse inequalities. However, it is necessary to improve prenatal care adequacy in SUS, considering that some studies showed worse performance compared to private prenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…This model is composed of three phases: phase I -delay in decision to seek care by the individual and/or family, phase II -delay in reaching an adequate health care facility, and phase III -delay in receiving adequate care at the health facility. Phase III delay in terms of early diagnosis of the complications and time to start appropriate management are crucial factors in minimizing the mortality and morbidity [14].…”
Section: Discussionmentioning
confidence: 99%
“…No Rio Grande do Norte, Brasil, um estudo realizado entre outubro de 2013 a setembro de 2014, que contou com 492 mulheres, evidenciou como fator de risco, além de condições clínicas que corroboram as pesquisas já citadas, um número de consultas de pré-natal inferior ao preconizado (OR=5,0; RP=4,2; IC95% 2,5-9,7) e a via de parto cesárea (OR=39,2; RP=31,2; IC95% 9,3-164,5) (17) . Esse achado é corroborado por outros estudos que associam a ausência de cuidados pré-natais com aumento no risco de desenvolver uma ocorrência de Near Miss (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) . Um estudo de caso-controle realizado no Marrocos, com 299 mulheres, em 2012, encontrou uma incidência de Near Miss Materno de 12/1.000 nascidos vivos, com proporção maior para os seguintes fatores de risco quando comparados ao grupo controle: analfabetismo (65% versus 22%, p<0,001); baixo nível socioeconômico (42% versus 10%, p<0,001); história de aborto prévio (21% versus 7%, p<0,001); maior ocorrência de complicações na gravidez (51% versus 19%, p<0,001), e, por fim, menor proporção de mulheres com Near Miss teve acesso aos cuidados de saúde dentro de 24 horas do início de trabalho de parto (19% versus 67%).…”
Section: Fatores Determinantes Da Morbidade Materna Grave (Mmg)unclassified
“…Mulheres com menos anos de estudo apresentaram 2,06 vezes mais chance de chegarem ao hospital em estado grave, ou seja, a disfunção orgânica na chegada ou dentro de 24 horas (OR= 2,06, IC 95% 1,36-3,10) (24) . Esses achados são corroborados por outros estudos (18)(19)(20)(21)(22)(23)(24) . Com relação às variáveis sociodemográficas, encontrou-se um maior risco para o desenvolvimento da condição de Near Miss Materno em pacientes casadas (OR=7,9; RP=7,1; IC95% 2,4-26,1), com ensino médio incompleto (OR=3,1; RP=2,8; IC95% 1,6-6,0), procedente do interior (OR=4,6; RP=4,0; IC95% 2,1-10,0) e renda familiar menor que um salário mínimo (OR=7,0; RP=5,5; IC95% 3,6-13,6).…”
Section: Fatores Determinantes Da Morbidade Materna Grave (Mmg)unclassified